Association of genetic profile with muscle mass gain and muscle injury prevention in professional football players after creatine supplementation - Varillas-Delgado, D. (Nutrients, 2024)
Background: In recent years, the study of creatine supplementation in professional athletes has been of great interest. However, the genetics involved in response to supplementation is unknown. The aim of this study was to analyse, for the first time, the relationship between muscle performance-related genes and the risk of an increased body mass index (BMI) and muscle mass and a decrease in fat mass in professional football players after creatine supplementation.